Pharmacokinetics and Bioequivalence of Rasagiline Tablets in Chinese Healthy Subjects Under Fasting and Fed Conditions: An Open, Randomized, Single-Dose, Double-Cycle, Two-Sequence, Crossover Trial - Li, Yinjuan; Qi, Lu; Bai, Haihong; Liu, Ying; Fan, Rongxia; Tu, Yongrui; Sun, Yongqiang; Wang, Juxiang; Qi, Qi; Feng, Xiaohui; Zhou, Da; Wang, Xinghe (Frontiers in Pharmacology, 2020)
Objective: This study evaluated the pharmacokinetics, safety, and bioequivalence (BE) of two formulations of rasagiline tablets in healthy Chinese subjects under fasting and fed conditions. Methods: An open, randomized, single-dose, double-cycle, two-sequence, self-crossover pharmacokinetic study in healthy Chinese subjects under fasting and high-fat postprandial conditions was performed. A total of 108 healthy subjects (36 in the fasting group and 72 in the postprandial group) were recruited. In each cycle of the study under both conditions, subjects received a single oral dose of 1 mg of a test or reference preparation of rasagiline tablets (1 mg each). A washout period of 3 days was observed. Blood samples were obtained up to 10 h post-intake. Primary endpoints were the BE of major pharmacokinetic parameters (AUC0–t and AUC0–∞) and the maximum observed serum concentration (Cmax). Secondary endpoints were safety parameters. Results: The 90% confidence interval (CI) of the geometric mean ratio (GMR) of the test drug vs. the reference drug for rasagiline was 94.16–105.35% for the AUC0–t under fasting conditions and 99.88–107.07% under postprandial conditions. The 90% CIs for the AUC0–∞ were 93.55–105.01% and 99.59–107.05% under fasting and postprandial conditions, respectively. The 90% CIs for the Cmax were 88.26–108.46% and 89.54–118.23% under fasting and postprandial conditions, respectively. The 90% CIs for the test/reference AUC ratio and Cmax ratio were within the acceptable range (0.80–1.25) for BE. In this BE study, there were no serious adverse events (AEs). Conclusion: BE between the test and the reference products was established in both fasting and postprandial conditions. The two formulations of rasagiline showed good tolerability and a similar safety profile. Clinical Trial Registration:chinaDrugtrials.org.cn, identifier CTR20181466.